Inclusive Policy Design for Transformative Education: A Global Synthesis of Teacher Identity Formation in Resource-Constrained Contexts - Fitriyah, Aidatul (Yayasan Sinergi Kawula Muda, 2025)
This study explores how teacher professional identity and autonomy evolve within global education systems undergoing sociopolitical, cultural, and technological change. Anchored in the Critical Agency Framework, the study synthesizes recent empirical and theoretical research to examine how policy structures, cultural norms, and digital infrastructure shape teacher agency. It highlights how teachers navigate professional expectations within centralized systems, community traditions, and resource disparities. This study employed a hybrid approach integrating systematic review protocols with narrative synthesis. Academic sources were retrieved from Scopus, PubMed, and Google Scholar using structured searches and citation tracking. Peer-reviewed studies were selected for relevance to teacher identity and autonomy, covering diverse contexts including Mexico, Vietnam, China, and Finland. The findings highlight the necessity of integrated policy approaches that treat teachers as co-constructors of reform and recognize the socio-cultural and infrastructural contexts in which they operate. Effective educational change depends not only on institutional mandates but on authentic collaboration, cultural responsiveness, and investments in teacher capacity. This study contributes to the literature by offering a global, multi-layered analysis of how systemic structures shape the lived professional experiences of teachers. It underscores the importance of moving beyond one-size-fits-all policy frameworks and calls for adaptive, inclusive, and equity-driven reforms.